408 Hand Trauma Consent. (4th May 2021) - Masterton, G; Aly, R; Siddiqui, A; Talwar, C; Talwar, C
Abstract: Background: Consenting patients for procedures is a regular process for a trainee surgeon. The process of consent has come under scrutiny in recent years due to inadequacies highlighted by legal cases. With over 1.36 million patients attending A&E per year with hand trauma, this is the most common acute referral to Plastic surgeons. Aim: To review current local practice by auditing risks and complications from hand trauma consent forms. To develop and implement a standardised pre-printed label including relevant risks and complications for hand trauma. Method: Sample of hand trauma related consent forms audited assessing and comparing the risks and complications sections to a standardised set agreed locally by Consultant Plastic surgeons, cross referenced with literature. Standardised label including relevant risks and complications put into practice then re-audit their use. Results: Use of the new standardised label demonstrated an elimination of omissions and increased adherence to 100% for all the relevant risks and complications. Conclusions: Significant improvements in the process of consent were achieved through the development and implementation of a standardised risk and complications label. This ensures standards from the GMC and RCS guidelines are satisfied; positively impacting on service provision by improving the quality of the consent process.